A Comparison of Airline Safety Videos in Information Acquisition. (September 2017) - Ragan, Allison; Sommer, Tessa; Drews, Frank
This study examined the effect of humor on airline safety information retention. Passenger attention to pre- flight safety demonstrations is low, even though it may impact the chance of survival in an aviation accident. Airlines have employed humor and entertainment to educate passengers on safety information. This study explored whether the humorous presentation increases retention of safety information, or if humor acts as a distraction from safety relevant information. Participants viewed two pre-flight safety demonstration videos (humorous and non-humorous) in counterbalanced order then answered short-answer questions about the content of the videos. Retention scores after viewing either type of video for the first time were the same. However, when a humorous video was shown prior to a standard safety video, retention scores for safety material dropped. These findings suggest that humorous safety demonstrations may be more effective, not because they are best at conveying information, but because passengers do not attend to standard videos if they have previously been exposed to a humorous version.